Gross international reserves accumulation management, and relation to debt - Dumlao, Luis F. (2013)
This paper narrates pertinent lessons learned from financial crises and how countries have responded to them. With lessons learned comes the reaction to accumulate gross international reserves (GIR). A strength-weakness-opportunity-threat (SWOT) assessment of the present level of GIR of the Philippines is presented. The GIR is also juxtaposed with the debt of the Philippines. It provides insight into whether the debt of the Philippines is more external or internal, and whether it is a problem at all. With the continuing accumulation of debt, its level may have reached the point of excess. The consideration is whether to shift from passive liquidity management to active investment seeking, external debt management, or active inclusion.
Keywords: External debts; Public debts; Foreign exchange reserves